Der Hochwasserschutz an der Gürbe - Salvisberg, Melanie (Wirtschafts-, Sozial- und Umweltgeschichte, 2017)
Out of a wide perspective, the study examines the development of flood control in the region of the river Gürbe in Switzerland from 1855 to 2010. It shows not only technical progresses, but also changes in philosophy. The author illustrates how concepts of flood control have been implemented, which expectations and hopes were connected with them, and what effects the activities of flood control had.